Pelatihan Model Pembelajaran Berdiferensiasi: Pendekatan Efektif Untuk Kebutuhan Belajar Siswa (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Differentiated learning respects students’ uniqueness and provides flexibility in the learning process. The objective of this Community Service Program (PkM) was to provide training on a differentiated learning model as an effective approach to meeting students’ learning needs. The PKM was implemented using lectures, discussions, and demonstrations. The stages included an initial assessment, lesson planning based on content, process, product, and learning environment differentiation. The initial or diagnostic assessment showed 100% learning readiness, 64.7% interest in football topics, and 79.4% preference for a demonstration-based learning style. In the content differentiation stage, students’ learning needs were mapped through quizzes and varied learning activities conducted outside the classroom. Process differentiation included the use of media and teaching methods tailored to the results of the initial assessment, while product differentiation demonstrated students’ understanding through learning outcomes, with average quiz results of 100% for dribbling, 80% for passing, and 100% for controlling skills, as well as performance demonstrations representing learning achievement outside the classroom. The differentiated learning model training proved effective in improving students’ concentration, imagination, and learning outcomes.